Dual-Wideband Transmissive Linear-to-Circular Polarization Converter - Nkimbeng, Cho Hilary Scott; Wang, Heesu; Park, Ikmo (ISAP 2024 - International Symposium on Antennas and Propagation, 2024)
This paper presents a design for a novel single-layer, dual-wideband linear-to-circular polarization converter. The unit cell features two identical, diagonally oriented C-shaped metallic strips, integrated with four outward-extending diagonal parasitic strips that enhance polarization conversion. Positioned on an ultra-thin single substrate, the converter achieves a 90° phase shift for polarization conversion across two frequency bands centered at 11.5 and 30.7 GHz. It also operates effectively over two distinct frequency ranges: 6.45 to 16.72 GHz (a fractional bandwidth of 89.3%) and 25.06 to 36.35 GHz (36.7%). The converter delivers consistent polarization performance over a wide range of incidence angles and high transmittance at both operating frequency bands.
Keywords: C-shaped; C-shaped metallic strip; Dual Band; Dual-wideband; Linear-to-circular polarization converter; Metallic strips; Polarization conversion; Polarization converters; Single layer; Wide-band; C-shaped metallic strips; dual band; linear-to-circular polarization converter; wideband